Gender & research: Brussels, 8 - 9 November 2001 ; [conference proceedings] - Maxwell, Linda; Slavin, Karen; Young, Kerry (Community research / European Commission, 2002)
Contents: Mitsos, Achilleas: Introduction. - 1. "A lot done, a lot still to do" (Onkelinx, Laurette. - McNally, Eryl Margaret). - 2. Ministerial Round Table (u. a. Prusa, Josef: National Contact Centre "Women and Science" of the Czech Republic. - Hennicot-Schoepges, Erna: Women and Science in Luxembourg. - Bladh, Agneta: Gender and science in Sweden. - Mabandla, Brigitte: Gender and research in South Africa). - 3. FIRST RESULTS FROM THE HELSINKI GROUP ON WOMEN AND SCIENCE. POLICY REVIEW AND INDICATORS (Rees, Teresa: First results from the Helsinki Group on Women and Science. Policy Review. - Springham, Ruth: Design and collection of statistical indicators on woman in science). - 4. GENDER IMPACT ASSESSMENT STUDIES. - Section 1. Quality of life and management of living resources (Bosch, Minneke: Woman, gender and the life sciences. Women's participation in the Quality of life programme. - Klinge, Ineke: Women, gender and the life sciences. Research for and about women. - Maguire, Peggy: Gender equity and health). - Section 2. User-friendly information society (Healy, Adrian: Report on the user-friendly information society Gender Impact Assessment Study). - Section 3. Competitive and sustainable growth (Prista, Luisa: Woman in Growth - Perspectives on gender equality in industrial research). - Section 4. Energy (Clancy, Joy: Engendering energy). - Section 5. Environment and sustainable development (Schultz, Irmgard/Hummel, Diana: Gender Impact Assessment Study on the Environment and sustainable development sub-programme). - Section 6. Confirming the international role of community research (Martin, Charlotte: The Gender Impact Assessment Study on the INCO programme. - Leigh-Williams, Stella: Comments on the INCO Gender Impact Assessment Study). - Section 7. Promotion of innovation and encouragement of participation of SMES (Aguirre, Maria: Gender Impact Assessment Study on "Innovation and SMEs". - Farnworth, Hilary: Women SMEs. Gender issues from WEEN and WomenCraft Projects). - Section 8. Improving Human Research Potential and the Socio-economic Knowledge Base (Braithwaite, Mary: Gender Impact Assessment Study on "Improving human potential and socio-economic knowledge". - Lykke, Nina: Response to the Gender Impact Assessment of "Improving human research potential and the socio-economic knowledge base". - Braithwaite, Mary: Gender Impact Assessment Study on "Improving human potential and mobility aspects ...